Investigation of soldering for crystalline silicon solar cells. Issue 4 (5th September 2016) - Yang, Hong; Wang, He; Cao, Dingyue
Abstract : Purpose: Tabbing and stringing are the critical process for crystalline silicon solar module production. Because of the mismatch of the thermal expansion coefficients between silicon and metal, phenomenon of cell bowing, microcracks formation or cell breakage emerge during the soldering process. The purpose of this paper is to investigate the effect of soldering on crystalline silicon solar cells and module, and reveal soldering law so as to decrease the breakage rates and improve reliability for crystalline silicon solar module. Design/methodology/approach: A microscopic model of the soldering process is developed by the study of the crystalline silicon solar cell soldering process in this work. And the defects caused by soldering were analyzed systematically. Findings: The defects caused by soldering are analyzed systematically. The optimal soldering conditions are derived for the crystalline silicon solar module. Originality/value: The quality criterion of soldering for crystalline silicon solar module is built for the first time. The optimal soldering conditions are derived for the crystalline silicon solar module. This study provides insights into solder interconnection reliability in the photovoltaic (PV) industry.